2011
DOI: 10.1080/03043797.2010.531695
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of educational factors promoting or discouraging the intent to remain in engineering by gender

Abstract: This study seeks to examine key extrinsic and intrinsic factors that encourage or discourage persistence in attaining an engineering degree and pursuing an engineering-related career among both male and female undergraduates. Quantitative and qualitative findings from nine participating undergraduate degree programmes reveal that career expectations formulated through educational experiences as undergraduates play a key role in motivating students. Among females, faculty interaction in the classroom, such as f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 12 publications
3
17
0
Order By: Relevance
“…Studies focusing on individuals consider students' initial attitudes, abilities, behaviors, skills, and previous experiences as possible influences on student persistence and gender differences (e.g., Felder & Brent, 2005;Fox et al, 2009;Jones, Paretti, Hein, & Knott, 2010). Other studies (Amelink & Meszaros, 2011;Seymour & Hewitt, 1997) focus on the teaching environment, classroom interactions, and academic engagement as determinants of student performance and persistence. We propose instead an interactionalist approach (Astin, 1993;Tinto, 1993), which combines individual and institutional factors, to explain student success and retention in higher education.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies focusing on individuals consider students' initial attitudes, abilities, behaviors, skills, and previous experiences as possible influences on student persistence and gender differences (e.g., Felder & Brent, 2005;Fox et al, 2009;Jones, Paretti, Hein, & Knott, 2010). Other studies (Amelink & Meszaros, 2011;Seymour & Hewitt, 1997) focus on the teaching environment, classroom interactions, and academic engagement as determinants of student performance and persistence. We propose instead an interactionalist approach (Astin, 1993;Tinto, 1993), which combines individual and institutional factors, to explain student success and retention in higher education.…”
Section: Introductionmentioning
confidence: 99%
“…Female students become less persistent in their engineering degree programs (that is, they leave more frequently) when they experience lack of support, subtle discrimination, or experience exclusion by gender-specific treatment by teachers and male peers in engineering learning environments (Seymour & Hewitt, 1997). If, however, females receive encouragement through positive faculty interactions (feedback, respectful treatment) in the classroom and social activities (study groups), they are more likely to persist (Amelink & Meszaros, 2011;Hewitt & Seymour, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The study by Cech et al (2011) discovered that the strongest psychosocial factor influencing the women students' intentions to remain in or leave engineering was their relatively lower confidence in their ability to carry out the requisite professional roles and competencies than men, rather than their plans to have a family. Amelink and Meszaros (2011) discovered that career expectations formulated through educational experiences as undergraduates play a key role in motivating students to stay in engineering. The slow progress in achieving gender equality in engineering has fuelled the discussions around the underrepresentation of women in the field ('why so few'), and the overall opinion is that in order to see desirable changes occur a rather long-term process of implementing various reforms, including addressing biases in society, is required (Moss-Racusin et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, problem solving and intellectual growth are especially increased for students of color [28] . More frequent contact with faculty has also been linked to self-efficacy among engineering students [23,25] .…”
Section: Interactions With Facultymentioning
confidence: 99%
“…Conversely, authors in one study found that interactions outside of ethnicity with faculty and peers were beneficial and increased underrerpresented students' confidence [22] . Overall, engineering students' interactions with faculty are vital for retention and persistence [23,24,25] and are especially critical for black and Latino students in ensuring their academic success [8,14,26,27] .…”
Section: Interactions With Facultymentioning
confidence: 99%